Variation of Calcium, N-acetylglucosamine, Glucosamine and Glucose Content during Molting Cycle of Mud Crab (Scylla serrata Forskål 1775) - Jintana Salaenoi; Jitlada Bootpugdeethum; Mingkwan Mingmuang; Amara Thongpan (Agriculture and Natural Resources, 2006)
Calcium, N-acetylglucosamine, glucosamine and glucose content in the tissues of mud crab (Scylla serrata Forskål 1775) during molting cycle were determined. The results showed that calcium in gill decreased gradually from intermolt (C) to the lowest level of 6,527 ppm at 2-day premolt (D3) and increased again from 6-h postmolt (A1) to the highest level of 24,058.50 ppm at 7-day postmolt (B2.3) which was similar in pattern to calcium in the integument but of which at lower range (1,360.10-8,044.30 ppm). The highest content in haemolymph was found at 2-day premolt (D3). Variation of Nacetylglucosamine, a major component of chitin, showed similar pattern to calcium. Their content in gill and integument decreased from intermolt (C) to premolt (D1-D3) and increased at postmolt stages (A1-B2.3) while the pattern was opposite to that found in haemolymph which increased at premolt (D1-D3) and decreased at postmolt stages (A1-B2.3). For glucosamine, however, the content was quite low in both gill and integument but was moderately high at late postmolt in haemolymph. Glucose, on the other hand, seemed to be quite stable throughout the molting cycle (averaged 0.8973 ± 0.1489 % mg) in integument, but the profiles in hepatopancreas and gill were similar having the highest level at 5-day postmolt (B2.2). Glucose in muscle was at its peak of 0.7265 ± 0.1016 % mg at 2-day premolt (D3) followed by the ten times high level in haemolymph of 12.2020 ± 0.4807 % mg at late postmolt (B2.1). Variations of calcium, N-acetylglucosamine, glucosamine and glucose content corresponded to the changing of chemical composition of the tissues during chitin degradation of the old shed, chitin biosynthesis, mineralization of the new structure and the transportation of these substances between tissues.